1993
DOI: 10.1002/jcp.1041540123
|View full text |Cite
|
Sign up to set email alerts
|

19F NMR studies of changes in membrane potential and intracellular volume during dexamethasone‐induced apoptosis in human leukemic cell lines

Abstract: The induction of apoptosis in leukemic cells by dexamethasone is well known, but the mechanism of this type of cell death and of dexamethasone resistance by some variants is still poorly understood. Apoptotic cell death is preceded by many changes in cellular properties, such as glucose metabolism, cell size, cell density, and others. In this study, 19F-NMR has been used to characterize changes in cell membrane potential and intracellular accessible volume during dexamethasone induced apoptosis. One dex-sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
(40 reference statements)
1
11
0
Order By: Relevance
“…We have indeed observed that after 24 h the reduction in PME level for CEM-C1 cells is essentially independent of dex incubation time. Another observation that suggests the arrest of apoptosis in CEM-C1 cells in the early stages, the Effects of Dex on Rote of C h a n g e of Pi for C E M p C early arrest of dex-induced change in membrane potential, has recently been reported (Adebodun and Post, 1993). That dexamethasone induced an alkaline shift in CEM-C7, CEM-C1, and CEM-4R4, but not in CEM-ICR27 cells, suggests that the alkaline shift is a receptor-mediated phenomenon.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We have indeed observed that after 24 h the reduction in PME level for CEM-C1 cells is essentially independent of dex incubation time. Another observation that suggests the arrest of apoptosis in CEM-C1 cells in the early stages, the Effects of Dex on Rote of C h a n g e of Pi for C E M p C early arrest of dex-induced change in membrane potential, has recently been reported (Adebodun and Post, 1993). That dexamethasone induced an alkaline shift in CEM-C7, CEM-C1, and CEM-4R4, but not in CEM-ICR27 cells, suggests that the alkaline shift is a receptor-mediated phenomenon.…”
Section: Discussionmentioning
confidence: 96%
“…Aspects of glucocorticoid-induced apoptosis that have been reported include the elevation of cytosolic Ca(I1) concentration, protein kinase C activation, altered level of protein and RNA biosynthesis, induction of specific endonuclease, increase in cell density, and the cleavage of nuclear chromatin at internucleosomal sites (Arends and Wyllie, 1991;Raff, 1992;Fesus et al, 1991;Williams, 1991;Gerschenson and Rotello, 1992;Kerr et al, 1972;Golstein et al, 1991;Zawydiwski et al, 1983;Wyllie, 1980;Cohen and Duke, 1984). Studies in our laboratory have reported differences in glucose metabolism between CEM-C1 and CEM-C7 cells (Post et al, 1992) and the alteration of membrane potential (Adebodun and Post, 1993) during dex-induced apoptosis in human leukemic cell lines.…”
mentioning
confidence: 98%
“…Cell cultures were stored and defrosted as previously reported (Adebodun and Post, 1993a). Cells were grown in Iscove's medium containing 5% heat-inactivated fetal calf serum (FCS) and antibiotics (100 units/mL penicillin ϩ 100 g/mL streptomycin).…”
Section: Materials and Methods Cell Cultures And Preparationsmentioning
confidence: 99%
“…The sensitivity of human leukemic cells to dex is mediated by the presence of functional glucocorticoid receptors, although some variants with functional glucocorticoid receptors (e.g., the CEM-C1 cell line) are known to exhibit resistance to dex (Post and Baum, 1990;Zawydiwski et al, 1983;Post et al, 1992). Some key features of apoptosis identified by various studies include the alteration in protein kinase C activity, alteration in glucose metabolism, increase in cell density (i.e., cell size shrinkage), alteration in cell membrane potential, elevation of cytosolic Ca (II) concentration, induction of specific endonucleases, alteration in phospholipid metabolism, reduction in the intracellular ATP level, altered level of protein and RNA biosynthesis, and the cleavage of nuclear chromatin at internucleosomal sites (Arends and Wyllie, 1991;Raff, 1992;Fesus et al, 1991;Williams, 1991;Kerr et al, 1972;Wyllie, 1980;Goldstein et al, 1991;Cohen and Duke, 1984;Post et al, 1992;Gerschenson and Rotello, 1992;Adebodun and Post, 1993a, 1995.…”
mentioning
confidence: 97%
“…On the contrary, FI of cyanic and merocyanic stains and anionic probes (ANS and oxolon stains) decreases with an increase in potentials. TMPs of various cells were intensely studied by using PFPs [7,12,14]. Values of Aqb of the mitochondrial and plasma membranes in lymphocytes, macrophages, hepatocytes, and adipocytes were determined.…”
mentioning
confidence: 99%